Peran Humas PT. Telekomunikasi Indonesia dalam Penanganan Gangguan Layanan Indihome - Khairunnisa Khairunnisa; Anisa Diniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research objective is to determine the role of public relations PT. Telkomunikasi Indonesia regarding efforts to deal with Indihome service disruptions. This study uses a post-positivism paradigm with a qualitative approach, and the type of research is descriptive. The results of the study show that they always respond to any complaints reported by customers about indihome services and utilize public relations strategies by applying the Morrisan and CRM concepts from De Wulf Gaby. Through this application it can be seen that the strategy formed by public relations, namely: Planning with the formulation of the main program, namely maximizing internal & external publications; Actuating in its implementation, public relations is assisted by other units according to their fields, so that problems can be resolved quickly and accurately; Controlling, namely supervising programs that are carried out properly so that they are according to plan; Evaluating by calculating the performance of the achievement of program implementation, namely OKR (Objective & Key Result). The conclusion of the research is that the public relations role of PT Telkomunikasi Indonesia has been going well. Keywords: PT. Telekomunikasi Indonesia Public Relations Role, Public Relations Strategy, Service Interruption